New Advancements in Prognostic Biomarkers for Upper Tract Urothelial Carcinoma - Shi, Xiaotong; Zhu, Guodong (Current Medicinal Chemistry, 2026)
As research on upper tract urothelial carcinoma (UTUC) has deepened, the value of biomarkers in the prognostic evaluation of UTUC has been gradually highlighted. As a high-grade epithelial tumor derived from the renal pelvis or ureter, UTUC has a significant prognostic challenge to patients, given its high invasiveness and recurrence rate for the formation of post-operative bladder cancer. To better predict the recurrence and metastasis risk of UTUC, this article provides a comprehensive review of hematologic, urologic, genetic, and histologic biomarker studies on the prognostic assessment of UTUC. This study covers a broad range of different kinds of biomarkers, as shown in the graphical abstract. By systematically analyzing these biomarkers, we will have a better understanding of the biological features of UTUC, and it will provide more comprehensive and accurate information for its prognostic assessment. This will not only help clinicians develop more precise treatment strategies, but also provide patients with more personalized rehabilitation recommendations.
Keywords: bladder cancer